Lavender essential oil ameliorates depression-like behavior and increases neurogenesis and dendritic complexity in rats. (14th May 2019) - Sánchez-Vidaña, Dalinda Isabel; Po, Kevin Kai-Ting; Fung, Timothy Kai-Hang; Chow, Jason Ka-Wing; Lau, Way Kwok-Wai; So, Pui-Kin; Lau, Benson Wui-Man; Tsang, Hector Wing-Hong
Graphical abstract: Highlights: Lavender essential oil (LEO) improved the depression behavior induced by corticosterone treatment. LEO reverted the CORT-induced decreased number of BrdU positive cells in the hippocampus and subventricular zone. LEO stimulated dendritic branching in the DCX positive cell cells in the hippocampus under high corticosterone conditions. Abstract: Depression is a major health issue that causes severe societal economic and health burden. Aromatherapy, a practice that uses essential oils for preventive and therapeutic purposes, represents a promising therapeutic alternative for the alleviation of depressive symptoms. Lavender essential oil (LEO) has been the focus of clinical studies due to its positive effect on mood. An animal model of chronic administration of high dose corticosterone to induce depression- and anxiety-like behavior and reduced neurogenesis was used to explore the biological changes brought by aromatherapy. Twenty-four adult male Sprague Dawley rats were randomly assigned into four groups: Control, corticosterone (Cort) group with high dose of corticosterone, LEO group with daily exposure to LEO by inhalation, and LEO + Cort. At the end of the 14-day treatment period, behavioral tests were carried out. Serum samples were collected 2–3 days after the 14-day period treatment and before perfusion to carry out biochemical analyses to measure BDNF, corticosterone and oxytocin. After perfusion, brains were collected for immunohistochemical analysis to detect BrdU and DCX positive cells in the hippocampus and subventricular zone. Results showed that treatment with LEO ameliorated the depression-like behavior induced by the chronic administration of corticosterone as observed in the LEO + Cort group. Cort treatment reduced the number of BrdU positive cells in the hippocampus and the subventricular zone. Treatment with LEO prevented the corticosterone-induced reduction in the number of BrdU positive cells (LEO + Cort group) demonstrating the neurogenic effect of LEO under high corticosterone conditions. Chronic administration of high dose of corticosterone significantly reduced the dendritic complexity of immature neurons. On the contrary, treatment with LEO increased dendritic complexity of immature neurons under high corticosterone conditions (LEO + Cort group). The improved neurogenesis and dendritic complexity observed in the LEO + Cort group demonstrated a clear restorative effect of LEO under high corticosterone conditions. However, 2–3 days after the treatment, the levels of BDNF were upregulated in the LEO and LEO + Cort groups. Furthermore, the concentration of oxytocin in serum, 2–3 days after the treatment, showed to be upregulated in the LEO group alone. The present study has provided evidence of the biological effect of LEO on neuroplasticity and neurogenesis. Also, this study contributes to the understanding of the mechanism of action of LEO in an animal model where depression- and anxiety-like behavior and reduced neurogenesis were induced by high corticosterone administration.